Critical Components for Spontaneous Activity and Rhythm Generation in Spinal Cord Circuits in Culture - Buntschu, Samuel; Tscherter, Anne; Heidemann, Martina; Streit, Jürg (Frontiers in Cellular Neuroscience, 2020)
Neuronal excitability contributes to rhythm generation in central pattern generating networks (CPGs). In spinal cord CPGs such intrinsic excitability partly relies on persistent sodium currents (INaP), whereas respiratory CPGs additionally depend on calcium-activated cation currents (ICAN). Here we investigated whether ICAN contributes to spontaneous rhythm generation in neuronal networks of the spinal cord. We used slice cultures of ventral and transverse slices from E13-14 embryonic rodent lumbar spinal cord on multielectrode arrays (MEAs). All cultures showed spontaneous bursts of network activity with intraburst oscillations that became more pronounced with block of glycine and NMDA receptors and blurred with block of GABA A receptors. Bursts were usually initiated through strongly interconnected trigger networks that were probably activated by neurons that showed asynchronous intrinsic activity after blocking synaptic excitation with the AMPA receptor antagonist CNQX. Such intrinsic activity was completely blocked at all electrodes by both the INaP blocker riluzole as well as by the ICAN blocker flufenamic acid (FFA) and the more specific TRPM4 channel antagonist 9-phenanthrol. All three antagonists also suppressed spontaneous bursting completely and reduced stimulus-evoked bursts to single spike responses. Other antagonists of unspecific cation currents or calcium currents had no suppressing effects on either intrinsic activity (gadolinium chloride) or spontaneous bursting (the TRPC channel antagonists clemizole and ML204 and the T channel antagonist TTA-P2). Combined patch clamp and MEA recordings showed that HB9 interneurons were activated by network bursts but could not initiate them. Together these findings suggest that spontaneous intrinsic spiking in spinal cord neurons and thereby the generation of network bursts is driven by the interplay between INaP through Na+-channels and ICAN through putative TRPM4 channels.